2014
DOI: 10.1111/rda.12412
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bull Sperm Kinematics after Single Layer Centrifugation

Abstract: The objective of this study was to evaluate bull sperm kinematics after centrifugation through a single layer of a colloid [Single Layer Centrifugation (SLC)]. Ejaculates from 20 bulls were extended and stored at 4-6°C for 24 h during transport to the laboratory for SLC through Androcoll-B, followed by measurement of sperm kinematics in all samples. Total motility (86% and 88% for uncentrifuged and SLC samples, respectively) and progressive motility (84% for both the groups) were similar (p > 0.05). In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
(18 reference statements)
4
11
1
Order By: Relevance
“…On the other hand, negligible effects were found on the other kinetic parameters in normal bulls, with the exception that ALH increased in CC samples, and the difference became significant after cryopreservation. Our findings were different to those reported in a previous study, in which total and progressive motility were found to be similar in samples untreated and centrifuged by single layer (SLC): sperm straightness, linearity, and beat cross frequency were significantly higher in SLC, whereas velocity of the average path, curvilinear velocity and amplitude of lateral head deviation all significantly decreased [ 37 ]. These differences in the kinematic aspect could be due to the treatment of the samples before analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, negligible effects were found on the other kinetic parameters in normal bulls, with the exception that ALH increased in CC samples, and the difference became significant after cryopreservation. Our findings were different to those reported in a previous study, in which total and progressive motility were found to be similar in samples untreated and centrifuged by single layer (SLC): sperm straightness, linearity, and beat cross frequency were significantly higher in SLC, whereas velocity of the average path, curvilinear velocity and amplitude of lateral head deviation all significantly decreased [ 37 ]. These differences in the kinematic aspect could be due to the treatment of the samples before analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have indicated that the use of colloid centrifugation resulted in an increasing of after thawing motility and VIAB of urospermic ejaculates treated with PureSperm [17]. A similar result was observed for hemospermic bull samples processed through Androcoll-B [50].…”
Section: Discussionsupporting
confidence: 86%
“…The present study observed a decrease in the average percentage of total sperm motility after SLC selection. Similar results were showed by Yulnawati et al (2014) on fresh samples, which suggests that SLC has an overall negative affect on the motility of bull sperm.…”
Section: Discussionsupporting
confidence: 88%
“…In 2006, a modified species‐specific single‐layer version of the density gradient used for separating spermatozoa within a semen sample, Androcoll, was created by Professor Jane Morrell (Clinical Sciences, Swedish University of Agricultural Sciences, Uppsala, Sweden; Morrell, Richter, et al, 2014; Yulnawati, Abraham, Laskowski, Johannisson, & Morrell, 2014). Its greatest advantage is the possibility of processing larger volumes of ejaculate compared to existing centrifuge‐separation methods, for example in the production of cattle (Goodla, Morrell, Yusnizar, Stålhammar, & Johannisson, 2014), boars (Morrell & Wallgren, 2011) and stallions (Johannisson et al, 2009; Morrell, Johannisson, Dalin, & Rodriguez‐Martinez, 2009).…”
Section: Introductionmentioning
confidence: 99%